OLAH GERAK KAPAL MV. BERNHARD SCHULTE DALAM KONDISI LIGHTSHIP SAAT MENGHADAPI HURRICANE MATTHEW - Suwiyadi; Suherman; Wibowo (Dinamika Bahari, 2018)
Based on Allianz report related to safety and shipping review 2016, mention about 5vessels are lost, capsized, and aground due to heavy weather and Huricane along 2015. AndSwedish Club Assurance mentioned 309 claims with amount USD172.000 along 2005-2013.One of the biggest Hurricane in 2016 is Hurricane Matthew. So this study aims to observethe correct maneuvers in lightship condition performed by MV.Bernhard Schulte officer toprevent six motions degree especially heavy rolling, that leads capsizing of te ship, duringHurricane Matthew. The method used in this study was qualitative phenomenology designwith analysis of triangulation data resources technique. The result shows (a) the shipmaneuvering was done with head seas in semi-circle navigable area by the use of waterstopography as shelter and supporter of ship maneuvering. The conclusion is using head andbow sea maneuvering method, even it is not recommended to be used on lightship condition.But the risk can be reduced by minimizing engine used, stability adjustment, and the use ofwaters topography.